PERBANYAKAN SERANGGA Helopeltis antonii SIGN. PADA BUAH KETIMUN DAN PUCUK JAMBU MENTE - DJATNIKA KILIN; WARSI RACHMAT ATMAJA (Jurnal Penelitian Tanaman Industri, 2000)
Rearing of Helopeltis antonii Sign (Hemiptera; Miridae) on cucumberfruit and cashew shootHelopeltis antonii is well known as a major pest of cashew, cacao and tea plantations A suficient number of the insect is frequently needed for esearch purposes. Rearing of // antonii on cucumber fruit was conducted from October 1997 to May 1998. Under laboratory condition. total eggs layed were 3.2 per female per day, while female longivity was 18.9 days. Egg period was 6.1 days and the total hatched was 93.5 percent. The egg and the irst unlil the ifth instar nymph periods were 6.1; 2.3; 2.0; 1.8; 1.9 and 3.2 days espectively. The adults emerged from earing of 10, 20 and 30 newly hatched nymph were 7. 13. and 17 insects or 71.3; 65.0, and 58.0 percent respectively. Eggs and nymph periods on cashew shoot almost the same as on cucumber fruit. The hatched eggs on cutted cashew shoot was 12 percent, while on the shoot of cashew seedlings was 89.0 percent This study indicated that cucumber fruit is very suitable and easier as well as more economical for mass rearing of // antonii.